Paganism, animism or Polytheism? an investigation into the labeling and categorisation of traditional belief system of the Kadazandusun - Low, Kok On; Sanen Marshall (2013)
The article surveys the difficulties associated with the attempts to describe the Kadazandusun belief system, which includes attempts to label it as pagan, animist or polytheist. The characteristics of the traditional Kadazandusun belief system are compared against these three concepts and the authors observe that both animistic and polytheistic elements are present. The authors highlight the fact that the Kadazandusun once believed in a hierarchy of deities. They show the similarities between Kadazandusun polytheism and the polytheistic forms of belief found in well-known civilisations such as Greece and China. Besides, the authors argue that the Kadazandusun are not pagan but they did posses their own belief system before the majority of them embraced the Christian and the Muslim faiths. By approaching the subject in this manner, it is hoped that a more accurate understanding of the traditional belief system of the Kadazandusun people can subsequently be obtained. More importantly, this article establishes beyond doubt that the traditional Kadazandusun do in fact posses system of belief, one that is a folk religion in its own right.